sFlt-1 Is an Independent Predictor of Adverse Maternal Outcomes in Women With SARS-CoV-2 Infection and Hypertensive Disorders of Pregnancy - Hernandez-Pacheco, Jose Antonio; Torres-Torres, Johnatan; Martinez-Portilla, Raigam Jafet; Solis-Paredes, Juan Mario; Estrada-Gutierrez, Guadalupe; Mateu-Rogell, Paloma; Nares-Torices, Miguel Angel; Lopez-Marenco, Mario Enmanuel; Escobedo-Segura, Keren Rachel; Posadas-Nava, Alejandro; Villafan-Bernal, Jose Rafael; Rojas-Zepeda, Lourdes; et al. (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (1). Pregnant women have a higher risk of severe COVID-19 (2, 3) caused by higher levels of inflammatory markers (IL-6, TNF-alpha, IFN-gamma, etc.), hypertension, oxidative stress, and thrombotic events causing multiorgan and placental damage with adverse outcomes for the mother and the developing fetus (4-7). Preeclampsia (PE) is defined as hypertension and proteinuria that debuts after 20 weeks gestation (8); its physiopathological pathway is similar to that of COVID-19, with an exaggerated inflammatory response that leads to endothelial damage and cytokine release from mesenchymal stromal cells of preeclamptic placentas (9, 10). In addition, there is an interaction between COVID-19 and PE, characterized by altered levels of angiogenic markers soluble fms-like tyrosine kinase (sFlt-1) and placental growth factor (PlGF) and higher sFlt-1/PlGF ratio (6, 11-13). Serum sFlt-1 is an antiangiogenic protein released from many tissues that antagonizes serum PlGF and vascular endothelial growth factor (VEGF), promoting endothelial dysfunction(14). Thus, PE and COVID-19 share a vascular–endothelial physiopathological pathway that may aggravate or worsen women’s outcomes when both coexist. We hypothesize that this synergic effect is exemplified in sFlt-1 levels among PE and COVID-19. In addition, there may be an interaction between hypertensive disorders of pregnancy (HDP), COVID-19, and sFlt-1 levels that reflect the incidence of adverse maternal outcomes (15). Therefore, this study aims to evaluate the association of sFlt-1 levels and adverse maternal outcomes among positive SARS-CoV-2 pregnant women with and without HDP.